Lifestyle entrepreneurship as a vehicle for leisure and sustainable tourism - Duarte, M.; Dias, Á.; Sousa, B.; Pereira, L. (International Journal of Environmental Research and Public Health, 2023)
The subject of this research is related to sustainable tourism and its connection with lifestyle en-trepreneurship. The Portuguese business fabric is formed by micro, small and medium sized en-terprises which have emerged in big numbers over the last years, mainly related directly and in-directly with the tourism industry. The discussed issue of this study will be if these companies are a vehicle for sustainable tourism in rural areas. Via a qualitative method, through comparative case study of eleven businesses, the goal is to evaluate if the lifestyle entrepreneurs’ initiatives promote sustainable tourism in rural areas, identifying the specific business created, evaluating their growth towards the planned strategies and actions related to internal resources and capacity, as well as in relation to marketing. Finally, the outcome will present the plans made for growth according to the necessary balance between economic progress, environment, public health and a social context. This study promotes decision tools for entrepreneurs and destination managers as to the practices to be adopted with the goal of sustainable development. Thus, in terms of ecological responsibility, the use of renewable energy through biomass is a very efficient practice because it both produces energy and reduces waste, since the energy production comes from plants and animal waste.